THE EFFECT OF THE PEROVSKY EXPEDITION ON THE TRADE RELATIONS OF THE KHIVA KHAN (International journal of artificial intelligence, 2024)
Czarist Russia experienced an industrial revolution at the beginning of the 19th century, and the demand for raw materials began to increase. The desire to conquer new territories, to create a large market from the conquered rich territories, to sell their industrial products duty-free, in addition, the memories of Bekovich-Cherkassky's expedition create a strong desire to occupy the Khanate of Khiva. For this purpose, the Perovsky expedition is organized. The results of the expedition, its impact on the embassy and trade relations are considered in this research paper.